Local health care expenditure plans and their opportunity costs. Issue 9 (September 2015) - Karlsberg Schaffer, Sarah; Sussex, Jon; Devlin, Nancy; Walker, Andrew
Highlights: We attempt to estimate the value of the threshold using data on marginal services. We also explore how the NHS makes decisions and the role of cost per QALY evidence. Cost per QALY estimates of services vary hugely and cannot reveal threshold. Cost-effectiveness evidence is rarely used to justify expenditure plans. Our results highlight the differences in objectives between HTA bodies and the NHS. Abstract: Background: In the UK, approval decisions by Health Technology Assessment bodies are made using a cost per quality-adjusted life year (QALY) threshold, the value of which is based on little empirical evidence. We test the feasibility of estimating the "true" value of the threshold in NHS Scotland using information on marginal services (those planned to receive significant (dis)investment). We also explore how the NHS makes spending decisions and the role of cost per QALY evidence in this process. Data and methods: We identify marginal services using NHS Board-level responses to the 2012/13 Budget Scrutiny issued by the Scottish Government, supplemented with information on prioritisation processes derived from interviews with Finance Directors. We search the literature for cost-effectiveness evidence relating to marginal services. Results: The cost-effectiveness estimates of marginal services vary hugely and thus it was not possible to obtain a reliable estimate of the threshold. This is unsurprising given the finding that cost-effectiveness evidence is rarely used to justify expenditure plans, which are driven by a range of other factors. Discussion and conclusions: Our results highlight the differences in objectives between HTA bodies and local health service decision makers. We also demonstrate that, even if it were desirable, the use of cost-effectiveness evidence at local level would be highly challenging without extensive investment in health economics resources.